Cost-utility analysis in orthopaedic trauma; what pays? A systematic review. Issue 3 (March 2018) - Coyle, S.; Kinsella, S.; Lenehan, B.; Queally, J.M.
Abstract: Background: As healthcare systems come under ever-increasing pressure to provide more care with fewer resources, emphasis is being placed on value-based systems that maximise quality and minimize cost. The aim of this study was to determine which interventions in fracture care have been demonstrated to be cost effective. Methods: A systemic review of cost-utility studies on the management of fractures from 1976 to 2015 was carried out using a search of the Cost-Effectiveness Analysis Registry, National Health Service Economic Evaluation Database (NHS EED) and MEDLINE. Results: 20 studies were included with 15 (75%) studies assessing interventions in lower limb trauma and 8 (25%) studies assessing interventions in upper limb trauma. 50% of studies used a decision tree model and 50% used collected data alongside a randomised clinical trial. Interventions which were shown to be cost effective in lower limb trauma were total hip replacement in displaced femoral neck fractures, the SHS in stable (A1 and A2) fractures and IM nailing for unstable (A3) fractures, salvage treatment for grade IIIB and IIIC open tibial fractures and operative treatment of ankle and calcaneal fractures. For systems-based strategies, there is evidence demonstrating cost effectiveness to treating hip fractures in high volume centres and to having resources in place to facilitate fractures being treated within 48 h of injury. In upper limb trauma there was evidence showing operative treatment of displaced proximal humerus fractures to be neither clinically nor cost effective. There was evidence supporting the operative treatment of non-displaced scaphoid fractures. Overall the quality of the studies was poor with only 50% (10) of studies able to make a treatment recommendation. Reasons for this included poor quality primary source data and poor reporting methodological practices. Conclusion: Certain aspects of fracture management have been shown to be cost effective. However, there is a paucity of evidence in this area and further research is required so that value-based interventions are chosen by healthcare providers engaged in orthopaedic trauma care.